Contour variation is a primary source of error when delivering post prostatectomy radiotherapy: Results of the Trans‐Tasman Radiation Oncology Group 08.03 Radiotherapy Adjuvant Versus Early Salvage (RAVES) benchmarking exercise. Issue 3 (5th April 2019) - Cloak, Kirrily; Jameson, Michael G; Paneghel, Andrea; Wiltshire, Kirsty; Kneebone, Andrew; Pearse, Maria; Sidhom, Mark; Tang, Colin; Fraser‐Browne, Carol; Holloway, Lois C; Haworth, Annette
Abstract: Introduction: Variation in target volume delineation from clinical trial protocols has been shown to contribute to poorer patient outcomes. A clinical trial quality assurance framework can support compliance with trial protocol. Results of the TROG 08.03 RAVES benchmarking exercise considering variation from protocol, inter‐observer variability and impact on dosimetry are reported in this paper. Methods: Clinicians were required to contour and plan a benchmarking case according to trial protocol. Geometric pjmirometers including volume, Hausdorff Distance, Mean Distance to Agreement and DICE similarity coefficient were analysed for targets and organs at risk. Submitted volumes were compared to a STAPLE and consensus 'reference' volume for each structure. Dosimetric analysis was performed using dose volume histogram data. Results: Benchmarking exercise submissions were received from 96 clinicians. In total 205 protocol variations were identified. The most common variation was inadequate contouring of the CTV in 84/205 (41%). The CTV volume ranged from 65.3 to 193.1 cm 3 with a median of 113.2 cm 3 . The most common dosimetric protocol variation related to rectal dosimetry. The mean submitted rectal volume receiving 40 Gy and 60 Gy, respectively, was 56.14% ± 5.55% and 30.25% ± 6.15%. When corrected to the protocol defined length the mean rectal volume receiving 40 Gy was 60.8% ± 7.92%, while the volume receiving 60 Gy was 33.86% ± 8.21%. Conclusion: Variations from protocol were found in the RAVES benchmarking exercise, most notably in CTV and rectum delineation. Inter‐observer variability was evident. Incorrect delineation of the rectum impacted on dosimetric compliance with protocol.